Analysis of Time and Cost Acceleration with Crashing Method on Apartment Construction Project in Bekasi City - Maddeppungeng, Andi; Asyiah, Siti; Intari, Dwi Esti; Ujianto, Rifky; Damanik, Mariana Feronica; Ashidiq, Alifian Taufiq (JURUSAN TEKNIK SIPIL, 2024)
In the implementation of construction projects, problems are often found, such as delays. One of the solutions is by accelerating. Acceleration is not only done to overcome delays, but can also be done if there is a special request from the owner. This study discusses the acceleration of time and cost using the crashing method in an apartment construction project in Bekasi City, which aims to determine the optimal time and cost of the three alternatives used. The work that is accelerated is some structural work that is on the critical path. Acceleration is carried out with three alternatives, namely the addition of working hours, the addition of labor, and the combination of additional working hours and additional labor. The results showed that with the alternative of adding working hours, the implementation time was 298 days at a cost of Rp. 140,751,032,332, obtaining a time efficiency of 5.7% and a cost efficiency of 0.42%. With the alternative of adding labor, the implementation time is 292 days at a cost of Rp. 140,092,976,595, 7.59% time efficiency and 0.89% cost efficiency are obtained. With the alternative of adding working hours and additional labor, the implementation time is 290 days at a cost of Rp. 139,912,527,724, 8.23% time efficiency and 1.02% cost efficiency are obtained. Then it can be concluded that the alternative with the most optimal time and cost is the combined alternative of adding working hours and adding labor.